2012
DOI: 10.1002/etc.2068
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of direct and trophic uranium exposures in the crayfish Orconectes limosus: Implication for predicting uranium bioaccumulation and its associated toxicity

Abstract: Abstract-Pollutants that occur at sublethal concentrations in the environment may lead to chronic exposure in aquatic organisms. If these pollutants bioaccumulate, then organisms higher in the food chain may also be at risk. Increased attention has thus been focused on the relative importance of dietary uptake, but additional knowledge of the cellular distribution of metals after dietary exposure is required to assess the potential toxicity. The authors address concerns relating to increasing uranium (U) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The cytosol fraction in gills represented between 13% and 30% of the total amount accumulated in the four subcellular fractions that is concordant with the suspected high fraction of adsorbed U on gill cuticle and also with the values found by Simon et al (2012) in their direct exposure study.…”
Section: Subcellular Levelsupporting
confidence: 83%
See 1 more Smart Citation
“…The cytosol fraction in gills represented between 13% and 30% of the total amount accumulated in the four subcellular fractions that is concordant with the suspected high fraction of adsorbed U on gill cuticle and also with the values found by Simon et al (2012) in their direct exposure study.…”
Section: Subcellular Levelsupporting
confidence: 83%
“…The pattern of U subcellular relative partitioning in hepatopancreas appears similar between the control and contaminated organisms, with a strong contribution of the cytosol fraction and a small contribution of the MRG fraction as shown by Simon et al (2012) in similar conditions of direct exposure. However, the influence of time duration on U distribution pattern within subcellular fractions between 30, 600 and 4000 lg L À1 groups can be due to the set-up of detoxification mechanisms more efficient at environmental levels than at high level of U exposure.…”
Section: Subcellular Levelmentioning
confidence: 63%
“…In the chronic experiment gills also accumulated more U than Cd possibly for the same reasons stated above. Recently, Simon et al () demonstrated that only 12% of total U accumulation in gills of crayfish O rconectes limosus after waterborne exposure was measured in the cytosol fraction which is considered as the potential toxic fraction. Authors stated that adsorption of U on the gills cuticle of O. limosus represented the main contribution of U accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many standard toxicology tests do not take trophic exposure into account, even though in controlled conditions it is easy to reproduce and interpret as a direct exposure standardized test [10]. Many standard toxicology tests do not take trophic exposure into account, even though in controlled conditions it is easy to reproduce and interpret as a direct exposure standardized test [10].…”
Section: Introductionmentioning
confidence: 99%
“…Trophic exposure was also selected because ecological risk assessments often focus on the relationship between direct exposure and the associated effects. Many standard toxicology tests do not take trophic exposure into account, even though in controlled conditions it is easy to reproduce and interpret as a direct exposure standardized test [10].…”
Section: Introductionmentioning
confidence: 99%